New IFAD Ethiopia office a 'milestone'—IFAD President Kanayo Nwanze - Nwanze, K. (International Livestock Research Institute, 2011)
On 11 August 2011, the International Fund for Agricultural Development (IFAD) opened a country office on the ILRI campus in Addis Ababa. Kanayo Nwanze, IFAD President, explains the importance of this 'milestone' - which offers greater opportunities for stronger partnership with research organizations and with the Government of Ethiopia.